Factors Associated with Daily Prenatal Care Practices: A Cross-Sectional Study at Berangas Public Health Center - Okvitasari, Yenny; Ruslinawati, Ruslinawati; Yuniarti, Kristina; Ash Shiddieqi, Hasbi; Pahliana, Pahliana; Hamsiah, Hamsiah; Wulandari, Ni Putu Cindy; Zinan, Rabiatul (Yayasan Ahmad Mansyur Nasirah, 2025)
Daily prenatal care plays an essential role in maintaining maternal and fetal health and preventing pregnancy complications. However, its implementation remains suboptimal due to several influencing factors. This study aimed to examine the relationship between maternal age, education level, parity, and family support with daily prenatal care practices. A cross-sectional study was conducted from May to June 2024 at Berangas Public Health Center, involving 74 pregnant women selected using purposive sampling. Data were collected through structured questionnaires and analyzed using Spearman’s rank correlation test. The research study shows that the majority of respondents were aged 20–35 years (86.5%), had education equivalent to senior high school or higher (56.8%), were in the at-risk parity group with 0, 1, and 3 live births (82.4%), and received adequate family support (82.4%). A total of 70.3% of respondents demonstrated good daily prenatal care practices. Significant positive correlations were found between age (ρ = 0.435, p < 0.001), education (ρ = 0.506, p < 0.001), and family support (ρ = 0.321, p = 0.005), while parity showed a significant negative correlation (ρ = –0.321, p = 0.005). These findings indicate that maternal education and family support are key factors influencing daily prenatal care behavior.